Surgical consequences in infants with delayed diagnosis of congenital chloride diarrhea - Al Awadhi, Haifa; Al Mehaidib, Ali; AlSaleem, Khalid; Banemai, Mohammed; Al Dekhail, Wajeeh (Turkish Journal of Gastroenterology, 2017)
Abstract Despite the usual typical presentation, congenital chloride diarrhea (CCD) poses multiple diagnostic challenges. It has an incidence of 1/5000 in Saudi Arabia. CCD can mimic intestinal obstruction and result in avoidable surgical interventions. Contributing factors are abdominal distension and the watery (urine-like) diarrhea that is often interpreted as delayed passage of meconium. Surgical interventions would unnecessarily increase the morbidity. Therefore, a high index of suspicion and educating neonatologists, general pediatricians, and pediatric surgeons regarding this diagnostic entity is essential. Here we describe five such cases. Cite this article as: Al Awadhi H, Al Mehaidib A, Al Saleem K, Banemai M, Al Dekhail W. Surgical consequences in infants with delayed diagnosis of congenital chloride diarrhea. Turk J Gastroenterol 2017; 28: 510-3.